Shaping the Effects of Associative Brain Stimulation by Contractions of the Opposite Limb - Carson, Richard G.; Rankin, Michelle L. (Frontiers in Psychology, 2018)
There has been an explosion of interest in methods that may promote neural plasticity by indirectly stimulating tissue in damaged brains using transient magnetic fields or weak electrical currents. A major limitation of these approaches is that the induced variations in brain activity tend to be diffuse. Thus far it has proved extremely difficult to target pathways from the brain to specific muscles. This is a particular challenge for applications in rehabilitation. Stroke survivors often exhibit abnormal patterns of muscle activation, including diminished specificity and high levels of co-contraction. For the clinical relevance of brain stimulation to be enhanced, it is desirable that the effects can be restricted to pathways controlling muscles that are the specific targets of movement therapy. We have demonstrated previously that increases in the excitability of corticospinal projections to forearm muscles generated by paired associative stimulation (PAS), are modulated by contractions ipsilateral to the site of the cortical stimulus. The current aim was to determine whether in chronic stroke survivors, simultaneous contractions performed by the non-paretic limb increase the muscle specificity of changes in the excitability of projections to the impaired limb induced by PAS. Ten chronic stroke survivors, thirteen age-equivalent and twenty-seven younger healthy controls, completed two separate sessions/conditions. In one (PAS+CONT), isometric wrist flexion contractions of the non-impaired limb were made simultaneously with PAS. In the other (PAS), associative stimulation only was applied. In all groups, PAS alone gave rise to large increases in the excitability of projections to a wrist extensor muscle (extensor carpi radialis - ECR) that was not the target of stimulation. In marked contrast, for the stroke survivors, following combined PAS and flexion contractions of the non-impaired limb, there was no corresponding elevation in the excitability of corticospinal projections to the ECR of the paretic limb. A similar effect was present for the healthy young adults, but not expressed clearly for the age-equivalent controls. The implications of these findings with respect to the clinical deployment of non-invasive brain stimulation in movement rehabilitation are discussed.